Phase Angle: Could Be an Easy Tool to Detect Low-Grade Systemic Inflammation in Adults Affected by Prader–Willi Syndrome? - Barrea, Luigi; Pugliese, Gabriella; de Alteriis, Giulia; Colao, Annamaria; Savastano, Silvia; Muscogiuri, Giovanna (Nutrients, 2020)
Prader–Willi syndrome (PWS) is the most common genetic inherited obesity syndrome. Obesity-related complications, mostly related to chronic low-grade systemic inflammation (LGI), are the commonest cause of mortality and morbidity in PWS adults. Phase angle (PhA) is an easy tool to screen a state of LGI in healthy subjects and in subjects with obesity and is obtained from bioelectrical impedance analysis (BIA). The aim of this study was to validate the PhA in PWS adults as a potential biomarker of LGI. In this single-center, cross-sectional study, fifteen PWS adults (six males, aged 19–41 years, and body mass index (BMI) 31.0–68.0 Kg/m2) and fifteen control subjects matched by gender, age, and BMI were evaluated. PhA values were significantly lower (p < 0.001), while high-sensitivity C-reactive protein (hs-CRP) levels were significantly higher (p < 0.001) in PWS adults compared with controls (p < 0.001), without a gender difference in the latter. After adjustment for gender, BMI, and waist circumference, significant correlation was found between PhA and hs-CRP levels (r = −0.69, p = 0.01). At the ROC analysis, the threshold value of PhA predicting the highest hs-CRP levels above the median value was found at PhA ≤ 4.8° (p = 0.01; AUC, 0.82; standard error, 0.12; 95% CI, 0.58 to 1.00). These results suggest that PWS adults had a significant higher degree of LGI compared with their counterparts. Moreover, our finding suggest that PhA is a valid biomarker of LGI also in PWS adults.